Three-dimensional range shifts in biodiversity driven by recent global warming - Haase, Peter; Li, Fengqing; Sundermann, Andrea; Lorenz, Armin; Tonkin, Jonathan; Stoll, Stefan (PeerJ Preprints, 2017)
Studies investigating changes in community composition in response to recent global warming are mostly restricted to one-dimensional (e.g. elevational or latitudinal) gradients, whereas species movements are in reality three dimensional (i.e. elevational, latitudinal and longitudinal). Based on 3,245 benthic invertebrate samples from Central European streams over large elevational, latitudinal and longitudinal gradients during the period from 1986 to 2009, we developed an advanced community temperature index (CTI). This CTI enables the analysis of three-dimensional community range shifts not only in freshwater but also in marine and terrestrial environments. Overall, in contrast to terrestrial communities, benthic invertebrate communities have been able to keep up with recent global warming. However, their ability to track temperature shifts differed grossly between the three spatial dimensions, with the strongest response to elevation. Nevertheless, the price these communities had to pay was high, as total benthic invertebrate abundance and richness in cold-dwelling species have already declined by 21% and 52.5%, respectively. Our approach emphasizes the complex reaction of aquatic communities towards increasing temperatures, allowing a more complete picture of the subtle community shifts in response to global warming.
Keywords: climate change; climatic debt; community temperature index; river; benthic invertebrates